The Perception Of English Teacher Association Pacitan About Good English Teacher - Kusaini, Nurnani, Prof.Dr.Endang Fauziati,M.Hum, Anam Sutopo Ph.D (2017)
The study aims to describe the English teachers` perception about good English teacher in terms of language competence, pedagogic, classroom management, interpersonal communication, and socio-affective competence. The research used a descriptive-qualitative method.The subjects are members of the English teacher association of Pacitan, consisting of 20 participants. The technique for collecting data includes open-ended question, interview and observation. The technique for data analysis applied reduction data, data display, conclusion drawing / verification. The findings indicate that language competence includes mastering four skills; listening, speaking, reading and writing, master the teaching material, major basic and standard competencies , creative to develop material, provide clear and understanding model. While pedagogical competence: open the class to lead learners mind, describe the learning purpose, using IT to find the source and learning media, have methods and teaching models, creative and fun learning, master the theory and practice teaching, design the teaching materials, develop the creative learning media, adapt the materials to learners` intelligence, make creative lesson plan, master the evaluation and fair assessment.The next is classroom management competence: design the class comfort, control the students, educate discipline, attention to all students, make students involved class activity, manage the time well. Interpersonal communication competence: create the qualified relationship, provide time in or out of class, understand the students`psychology, have receivable communication style, and appreciate the students work. Socio affective competence: be patient and good model, find out all students names, motivate students to learn, communicate friendly, have a sense of humor, attractive appearance, solve the students` private problem, and appreciate all learners.